Asthma Risk Associated with Indoor Mold Contamination in Hispanic Communities in Eastern Coachella Valley, California. (15th October 2018) - Sinclair, Ryan; Russell, Charity; Kray, Genevieve; Vesper, Stephen
Abstract : Indoor mold contamination has been associated in many studies with an increased risk of asthma and respiratory illness. This study investigated indoor mold contamination and the prevalence of asthma/respiratory illness in two low-income, Hispanic communities, Mecca and Coachella City, in the Eastern Coachella Valley (ECV) of California. The study consisted of a questionnaire to assess asthma/respiratory illness and the quantification of mold contamination in house dust samples using the Environmental Relative Moldiness Index (ERMI) scale. About 11% of the adults and 17% of the children in both Mecca and Coachella City met our definitions of asthma/respiratory illness. The average ERMI values in Mecca and Coachella City housing (10.3 and 6.0, respectively) are in the top 25% of ERMI values for the United States (US) homes. Overall, the homes surveyed in these ECV communities had an average prevalence of occupant asthma of 12.8% and an average ERMI value of 9.0. The prevalence of asthma/respiratory illness in the Hispanic communities of Mecca and Coachella City and the mold contamination in their homes appear to be greater than the averages for the rest of the US. The higher levels of mold contamination in their homes appear to be associated with a greater risk of asthma/respiratory illness for these low-income, Hispanic communities.